You need to put the brackets in this properly:

[f(x + h) - f(x)]/h.

For both questions below, express the slope of the secant line of each function in terms of x and h. Be sure to simplify your answer.

(1) f(x) = -3x + 2

[f(x + h) - f(x)]/h=[(-3(x+h) + 2)-(-3x + 2)]/h=[-3h]/h=-3

(2) f(x) = 1/x

[f(x + h) - f(x)]/h=[(1/(x+h)-1/x]/h=[(x-(x+h))(x(x+h))]/h=-1/(x(x+h))

Definition of a secant line can be found here.Also, what exactly is the slope of the secant line?

What is a secant line anyway?

As it is a line its slope is defined as the tan of the angle that

the line makes with the horizontal.

RonL